2009
DOI: 10.1007/s10796-009-9184-x
|View full text |Cite|
|
Sign up to set email alerts
|

Examining influencing factors of post-adoption usage of mobile internet: Focus on the user perception of supplier-side attributes

Abstract: Key supplier-side factors that affect the usage level of mobile Internet were identified and the procedural mechanism among the independent and dependent variables was investigated. For this, a research model was introduced to describe associations among four external variables (access quality, service variety, cost rationality, and ease of use), an intermediate variable (usefulness) and a dependent variable (the usage level of mobile Internet). Through the on-line survey, data were gathered from actual mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 55 publications
(92 reference statements)
5
62
0
Order By: Relevance
“…Already MI has become a platform for popular applications such as instant messaging, online gaming, multimedia (e.g., video and audio streaming), financial services (e.g., banking), search, and mapping and location-based services [7]. This paper is the first systematic attempt to examine patterns of mobile cellular adoption and MI use in US counties.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already MI has become a platform for popular applications such as instant messaging, online gaming, multimedia (e.g., video and audio streaming), financial services (e.g., banking), search, and mapping and location-based services [7]. This paper is the first systematic attempt to examine patterns of mobile cellular adoption and MI use in US counties.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…In the context of this research, mobile internet (MI from this point forward) is defined as Internet access through the cellular phone infrastructure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Korhonen et al [12] surveyed mobile users and concluded that the mobile device, task at hand and social context are the most influencing factors of the user's QoE. Similarly, Park et al [13] indicated usability, usefulness and affect as the factors, and Shin et al [14] added enjoyment, as well as network access quality to this list. Reichl et al [3] attempt to evaluate QoE in real user environments by capturing user interaction with the mobile phone, as well as the user context using two different cameras mounted on a large female hat worn by the user.…”
Section: Related Workmentioning
confidence: 99%
“…Perceived usefulness has been found to be a significant factor affecting initial usage and continuance usage (Venkatesh & Davis, 2000). Much research has reported the effects of initial trust and perceived usefulness on behavioral intention (Chen & Barnes, 2007;Shin, Lee, Shin& Lee, 2010).…”
Section: Usage Intentionmentioning
confidence: 99%